The path of canine visceral leishmaniasis versus the path of Center for Zoonoses Control: contributions of spatial analysis to health - Matsumoto, Patricia Sayuri Silvestre [UNESP]; Flores, Edilson Ferreira [UNESP]; Barbosa, José Seguinot; Pessoto, Umberto Catarino; Tolezano, José Eduardo; Hiramoto, Roberto Mitsuyoshi; Taniguchi, Helena Hilomi; Guimarães, Raul Borges [UNESP] (My University, 2022)
Visceral leishmaniasis (VL) is a public health problem in Brazilian municipalities. As much as there is a planning of public policies regards VL in São Paulo State, new cases have been reported and spread. This paper aims to discuss how the Center for Zoonoses Control conducts its actions spatially in endemic city of Presidente Prudente, São Paulo State. Data are from the Municipal Health Department of Presidente Prudente, Adolfo Lutz Institute, and Brazilian Institute of Geography and Statistics. We spatially estimated the dog population per census tract and used geoprocessing tools to perform choropleth maps, spatial trends, and spatial autocorrelation. We found a spatial pattern of higher prevalence in the city's outskirt and a positive statistically signifi-cant spatial autocorrelation (I = 0.2, p-value < 0.000) with clusters of high-high relationships in the Northwest part of the city. Moreover, we identified a different direction in the path of the conducted serosurveys versus the canine VL trend, which stresses the fragility of the Center for Zoonoses Control actions to control the disease. The Center for Zoonoses Control always seems to chase the disease. The spatial analysis may be useful for rethinking how the service works and helps in public policies.
La trayectoria de la leishmaniasis visceral canina versus la trayectoria del Centro para el Control de Zoonoses: contribuciones del análisis espacial a la salud
O caminho da leishmaniose visceral canina versus o caminho do Centro de Controle de Zoonoses: contribuições da análise espacial para a saúde
Keywords: Decision-making; Epidemiologic surveillances; Visceral leishmaniasis